2020
DOI: 10.1038/s41598-020-60293-y
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Crocetin across the Blood-Brain Barrier by Using γ-Cyclodextrin to Treat Alzheimer’s Disease

Abstract: Crocetin (CRT) has shown various neuroprotective effects such as antioxidant activities and the inhibition of amyloid β fibril formation, and thus is a potential therapeutic candidate for Alzheimer's disease (AD). However, poor water solubility and bioavailability are the major obstacles in formulation development and pharmaceutical applications of cRt. in this study, a novel water-soluble cRt-γcyclodextrin inclusion complex suitable for intravenous injection was developed. the inclusion complex was nontoxic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…A more quantitative estimation of the neuroprotective effect of trans-crocetin against H 2 O 2 damage is provided by a viability test of the increasing concentration of trans-crocetin ( Figure 3b). In agreement with previous reports [17,18], the investigation evidenced that this natural molecule is able to counteract H 2 O 2 neurotoxicity, preserving cell viability. As expected, oxidative stress due to treatment with H 2 O 2 caused a significant decrease of cell viability of 48% ± 3%.…”
Section: Anti-oxidative Effect Of Trans-crocetin By Means Of Membranesupporting
confidence: 92%
See 1 more Smart Citation
“…A more quantitative estimation of the neuroprotective effect of trans-crocetin against H 2 O 2 damage is provided by a viability test of the increasing concentration of trans-crocetin ( Figure 3b). In agreement with previous reports [17,18], the investigation evidenced that this natural molecule is able to counteract H 2 O 2 neurotoxicity, preserving cell viability. As expected, oxidative stress due to treatment with H 2 O 2 caused a significant decrease of cell viability of 48% ± 3%.…”
Section: Anti-oxidative Effect Of Trans-crocetin By Means Of Membranesupporting
confidence: 92%
“…Within the scenario of new molecules able to reverse neurodegeneration, emerging paths include the use of natural compounds with promising therapeutic potential. To this purpose, insulted neurons were treated with different concentrations of carotenoid trans-crocetin, which has several pharmacological properties [16][17][18][19]. Nevertheless, its neuroprotective role in counteracting neurodegeneration is poorly understood and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…CD-based materials are attractive for biomedical use due to being highly biocompatible, demonstrating low toxicity and immunogenicity in long-term release applications [35,36]. Specific to our current study, CD has been used for neuronal applications with no associated neurotoxicity [37][38][39]. In fact, CDs have been found to be a neuroprotectant and reduce neurotoxicity [37][38][39].…”
Section: Introductionmentioning
confidence: 91%
“…This problem may be solved with cyclodextrins or similar molecules. For example, Wong et al suggested that crocetin- γ -cyclodextrin inclusion complex could enhance the solubility, bioavailability, and applicability of crocetin [ 33 ]. Puglia et al showed that solid lipid nanoparticles containing crocetin improved its solubility, stability, and pharmacokinetic properties, offering an appropriated approach to resolve this issue [ 34 ].…”
Section: Discussionmentioning
confidence: 99%